Seed storage and acclimatization of Brassavola tuberculata Hook - Macedo, Marichel Canazza; Rosa, Derek Brito Chaim Jardim; Soares, Jackeline Schultz; Tatara, Mariana Bento; Hoffmann, Nilda Tiyoko Kobayashi; Rosa, Yara Brito Chaim Jardim (Semina: Ciências Agrárias, 2014)
In vitro sowing and acclimatization of the produced plantlets are responsible factors for the successful production of Orchidaceae. This study aimed to: 1) evaluate the viability of B. tuberculata seeds stored at different temperatures, and 2) evaluate the ex vitro growth of B. tuberculata on different substrates. The seeds were stored for 84 days under three conditions: ambient temperature (23 Â± 2 Â° C), refrigerator (4 Â± 2 Â° C) or freezer (-14.5 Â± 2 º C). The completely randomized design was used and treatments were arranged in a 3 (temperature conditions) x 6 (storage period) factorial scheme with three replications. Seed viability was determined by tetrazolium test. For acclimatization, two-year plants coming from in vitro sowing were acclimatized in plastic trays containing: 1 - sphagnum; 2 - charcoal or 3 - coconut fiber. We used the completely randomized design with 3 treatments and 4 replications of 10 plants each. The plants remained in the greenhouse for 365 days under ambient conditions, receiving daily average brightness of 130 ?m-2 s-2. After this period, the plants were evaluated for survival percentage, fresh and dry weight of shoots and roots, and it was calculated the relationship between fresh weight of the plants, the shoot length and the largest root, the number roots and the number of tillers, observed at the end of the experimental period compared to those recorded at planting. For the seed study, after 84 days seeds stored under ambient conditions showed 0.0% viability, while those stored in the refrigerator and freezer showed 77.6 and 67.2% viability. At the end of the acclimatization period, all the relations between the initial and final values were greater than 1.00 indicating that the conditions presented by the three substrates led to the growth of the species, and the percentage of plant survival was around 89%. We conclude that the B. tuberculata seeds should be stored in the refrigerator and that the studied substrates can be used in the acclimatization plants of B. tuberculata.